2010
DOI: 10.1002/jssc.201000234
|View full text |Cite
|
Sign up to set email alerts
|

Infrared‐assisted extraction coupled with high‐performance liquid chromatography for simultaneous determination of eight active compounds in Radix Salviae miltiorrhizae

Abstract: In this study, a novel infrared-assisted extraction (IRAE) method, in which infrared radiation was employed to extract the active compounds from plant, was developed and coupled with HPLC for simultaneous determination of four phenolic acids and four diterpenoids in Radix Salviae miltiorrhizae (Chinese name Danshen). The extraction conditions of IRAE were optimized and the optimal conditions were as follows: extraction time of 15 min; extraction solvent of 70% v/v methanol in water solution, and solid/liquid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 31 publications
1
33
0
1
Order By: Relevance
“…Like microwaveassisted extraction (MAE), the ability to rapidly heat the sample solvent mixture is inherent to IRAE. By using closed vessels, the extraction can be performed at elevated temperatures accelerating the mass transfer of target compounds from the sample matrix (Chen, Duan, Xie, & Li, 2010). In my study, the temperature of the IRAE was measured, and the mixed solvent reached the boiling point (79°C) within 7 min, while with the classical electrical heating method the temperature increased slower and reached the boiling point (79°C) at 13 min.…”
Section: Comparison Of Different Extraction Methodsmentioning
confidence: 88%
“…Like microwaveassisted extraction (MAE), the ability to rapidly heat the sample solvent mixture is inherent to IRAE. By using closed vessels, the extraction can be performed at elevated temperatures accelerating the mass transfer of target compounds from the sample matrix (Chen, Duan, Xie, & Li, 2010). In my study, the temperature of the IRAE was measured, and the mixed solvent reached the boiling point (79°C) within 7 min, while with the classical electrical heating method the temperature increased slower and reached the boiling point (79°C) at 13 min.…”
Section: Comparison Of Different Extraction Methodsmentioning
confidence: 88%
“…To date, several studies on pharmacokinetics of GA in its pure form have been reported. 4,[6][7][8] However, to the best of our knowledge, no study on pharmacokinetic behaviors of GA after oral administration of Changtai Granule has ever been reported.…”
Section: Kineticsmentioning
confidence: 99%
“…Thus, most scientists hope to increase understanding of mechanisms of Danshen by analyzing active components of Danshen . Presently, many active components have been isolated and identified in Danshen , such as tanshinone IIA, and salvianolic acid B (SA-B) [12-14]. …”
Section: Introductionmentioning
confidence: 99%